Wireless Power Transfer in Electrical Vehicle by Using Solar Energy - Uthaya Banu, N.; Arunkumar, U.; Gokulakannan, A.; Hari Prasad, M.K.; Sharma, A.B. Shathish (Asian Journal of Electrical Sciences, 2018)
Wireless Power Transfer[WPT] using the magnetic induction technology which could avoid human from the hazardous accident caused due to the using of cables. By the using of MOSFET switches in the inverter, it creates the output with high frequency improves the efficiency of power transfer between the coils. Due to this creation of output with higher frequency the charging of battery will be very fast and efficient. By connecting the solar panel to the supply battery, it will be charged continuously using this panel. This will helps the users for the non-stop driving. These advances make the WPT very attractive to the electric vehicle charging application in both stationary and dynamic charging. By introducing WPT in electric vehicle, the obstacles of charging time, range, and cost can be easily managed. WPT technology is developing rapidly in recent years.